2016
DOI: 10.1016/j.bbamcr.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of angiotensin II type 1 receptor in breast cancer cells induces epithelial–mesenchymal transition and promotes tumor growth and angiogenesis

Abstract: The angiotensin II type I receptor (AGTR1) has been implicated in diverse aspects of human disease, from the regulation of blood pressure and cardiovascular homeostasis to cancer progression. We sought to investigate the role of AGTR1 in cell proliferation, epithelial-mesenchymal transition (EMT), migration, invasion, angiogenesis and tumor growth in the breast cancer cell line MCF7. Stable overexpression of AGTR1 was associated with accelerated cell proliferation, concomitant with increased expression of surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…Interestingly, angiotensin II-mediated stimulation significantly increased VEGFA gene expression only in ER −ve cell lines, which was completely inhibited by the ARB, Candesartan [38]. A recently published study also confirms a pro-tumourigenic role of AT 1 R demonstrating that overexpression of AT 1 R in an ER +ve breast cancer cell line resulted in increased proliferation, increased expression of poly(ADP-ribose) polymerase (PARP) and X-linked inhibitor of apoptosis (XIAP), increased ERK, p-Smad3/4 activation [39]. Furthermore, treatment with Losartan attenuated these effects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, angiotensin II-mediated stimulation significantly increased VEGFA gene expression only in ER −ve cell lines, which was completely inhibited by the ARB, Candesartan [38]. A recently published study also confirms a pro-tumourigenic role of AT 1 R demonstrating that overexpression of AT 1 R in an ER +ve breast cancer cell line resulted in increased proliferation, increased expression of poly(ADP-ribose) polymerase (PARP) and X-linked inhibitor of apoptosis (XIAP), increased ERK, p-Smad3/4 activation [39]. Furthermore, treatment with Losartan attenuated these effects.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, treatment with Losartan attenuated these effects. Overexpression of AT 1 R also accelerated tumor growth, increased tumor angiogenesis, enhanced tumor invasiveness as demonstrated by increased expression of EMT markers including matrix metallopeptidase 9 (MMP-9) and reduced E-cadherin [39]. Collectively these studies identify the mechanisms via which AT 1 R facilitates tumor growth and invasiveness in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It reported that AGTR1 could regulate blood pressure and promote angiogenesis [26]. MYLK can encode smooth muscle and nonmuscle isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures were performed as previously described . The primary antibody dilutions were [phospho‐Histone H3 (Ser10, 1:2000), β‐tubulin (1:2000), STAT3 (1:2000) phospho‐STAT3 (Tyr705, 1:2000), PARP (1:2000), cleaved‐PARP (1:2000), cleaved‐caspase 3 (1:1000), cleaved‐caspase 7 (1:1000), CD49f (1:2000), ALDH1A1 (1:2000), cyclin D1 (1:2000), survivin (1:2000) and actin (1:5000)] and membranes were incubated with HRP‐conjugated rabbit or mouse secondary antibodies (1:3000–1:10,000).…”
Section: Methodsmentioning
confidence: 99%